THE ROLE OF A NOTARY IN THE PROCEDURE FOR IMPLEMENTING A SHARE ACQUISITION OF A LIMITED LIABILITY COMPANY - Juliane Chaerunnisa; Mella Ismelina Farma Rahayu (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
: There are several types of business entities regulated in Indonesia, one of which is a Limited Liability Company which is the most common business entity that can be found, in the form of a legal entity and in carrying out its business activities has an authorized capital divided into shares. One of the actions commonly taken by a Limited Liability Company is to acquire shares, otherwise known as acquisition. This acquisition process requires several steps or procedures that need to be fulfilled and has been regulated in Law Number 40 of 2007 concerning Limited Liability Companies.An act of acquisition is administratively declared complete if it has been set forth in a deed of acquisition made by an authorized officer, namely a notary in the Indonesian language and submission of notification to the Minister of Law and Human Rights. Notary as a profession that is authorized to make authentic deeds that can be used as evidence in court has a role and responsibility for the documents it issues, including the deed of acquisition of a Limited Liability Company. This paper is designed to review the acquisition procedure of a Limited Liability Company and the role of a Notary in that procedure in relation to his or her authority to draw up a deed of acquisition